Epidural analgesia for painless labour and its impact on neonatal outcome - Amrita Chaurasia; Nidhi Sachan; Neelam Singh (Barpeta Obstetrics and Gynaecological Society, 2021)
Objectives: To evaluate the effectiveness of epidural labour and its impact on maternal and neonatal outcome. Methods: Epidural analgesia was given to 50 patients and 50 were chosen as control with no analgesia. All the patients in the study were primi, with vertex presentation, with no contraindication for vaginal delivery. Duration of labour, mode of delivery, assisted vaginal delivery, pain scores, fetal heart rate and Apgar score of neonates were assessed. Results: There was no statistical significance in the rate of caesarian section in both the groups (p = 0.69). Duration of second stage of labour was prolonged in study group, and the difference was statistically significant (p < 0.001). There was no difference in baseline fetal heart rate (FHR) in both the groups. There was a significant reduction in Vas (Visual analogue scale) score of the parturient in study group, with mean Vas score reaching < 1 in 30 minutes. There was no statistical difference in Apgar score of both the groups. Conclusion: Epidural analgesia is an effective way of painless labour, with no significant maternal and neonatal side effects.